Ekstrimisme Aturan Sosial Masyarakat Arab Pra Islam Ditinjau dari Nilai Moderat dan Toleransi - Nurfadhilah, Nurfadhilah; Erman, Erman; Hasnah, Radhiatul (TSAQOFAH, 2024)
This research is motivated by the system of social rules implemented by pre-Islamic Arab society. These social rules trigger problems in terms of gender equality and tolerance between humans. Even at that time, it was very easy to find practices of violence and war. All the problems that occurred were completely inconsistent with Islamic teachings, because they included inhumane acts. Based on this problem, pre-Islamic Arab society was known as a jahiliyah society. However, in today's advanced era, problems are still found that are similar to the pre-Islamic Arab era. Based on these circumstances, this article aims to explain a number of extremism problems originating from the inhumane social rules of pre-Islamic Arab society in terms of the values ​​of moderation and tolerance of Islamic teachings and the current reality. The method used is literature study for the pre-Islamic Arab period and direct observation of the social reality of today's society. The findings are first, insulting women and the practice of killing newborn female babies as well as slavery are considered immoderate and inhumane acts. Second, the habit of war extremism which was often carried out in pre-Islamic Arab society because of minor disputes between tribes, and was supported by the tribal fanaticism of society. Third, marriage practices and divorce provisions that were wrong and detrimental to women were carried out during the pre-Islamic Arab period. Fourth, the social reality of today's society still bears similarities to the pre-Islamic Arab period, which is caused by the lifestyle and application of Islamic teachings which are not optimal.